Influence of Al(Er) interlayer on the mechanical properties of AlN(Er) coatings - Oliveira, J. C. (2002)
AlN(Er) thin films were deposited by sputtering on M2 steel (AISI) and Si substrates with different thickness of an Al(Er) interlayer. No significant variations were observed in the chemical composition and structure of the AlN(Er) films. The films in all cases presented excess nitrogen in relation to AlN stoichiometry. The diffraction peaks were strongly shifted to lower angles due to the presence of Er. The hardness of the films is approximately 32 GPa and does not change with the thickness of the Al(Er) interlayer. The cohesion and adhesion of the AlN(Er) films were improved with the inclusion of the Al(Er) interlayer; the cohesive and adhesive critical load values increased from 7 and 17 N to 15 and 27 N, respectively.